Seed morphology of parthenocissus planch. and ampelopsis michx. (vitaceae) and its taxonomic significance - A. Latiff, (Universiti Kebangsaan Malaysia, 2012)
Morphological description of seeds of Parthenocissus and Ampelopsis is given and followed by a discussion of its taxonomic significance.